2020
DOI: 10.1007/s42977-020-00013-9
|View full text |Cite
|
Sign up to set email alerts
|

Biologia Futura: rapid diversification and behavioural adaptation of birds in response to Oligocene–Miocene climatic conditions

Abstract: Our knowledge about the origin of landbirds (Telluraves) is increasing rapidly but new questions are arising because of the contradictory findings from previous studies. All of the major lineages in the highly diverse clade of Neoaves have a Gondwanan origin, although studies often disagree about the origin of different sub-lineages. Nevertheless, understanding the biogeographical histories of these groups (e.g. Accipitriformes, Passeriformes) is important when studying the evolution of variation in life histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(86 reference statements)
2
6
0
Order By: Relevance
“…The earliest known Palaearctic remains come from the Upper Oligocene (MP 30) from sites at Coderet and Gannat (Allier) in France (Mourer-Chauviré et al 1989). Typically, these finds already bear the osteomorphological signs indicating passerines (Nagy 2020). Thereafter, fossils from Europe, Asia, and also from North and South America are only known from the Lower Miocene.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest known Palaearctic remains come from the Upper Oligocene (MP 30) from sites at Coderet and Gannat (Allier) in France (Mourer-Chauviré et al 1989). Typically, these finds already bear the osteomorphological signs indicating passerines (Nagy 2020). Thereafter, fossils from Europe, Asia, and also from North and South America are only known from the Lower Miocene.…”
Section: Introductionmentioning
confidence: 99%
“…The passerine clade (Passeriformes) comprises over half of all extant birds worldwide. The Gondwanan radiation of passerines firmly roots the origin of oscines in modern-day Australasia (Barker et al 2004;Nagy 2020), and the Australian avifauna still contains many endemic and phylogenetically distinct lineages that represent the earliest parts of the passerine radiation. Passeriformes subsequently further diversified when orders and families radiated out of Australasia, into Eurasia, Africa and the new world, as early as 55 million years ago (Barker et al 2004;Oliveros et al 2019;Nagy 2020).…”
mentioning
confidence: 99%
“…brood parasites, partners or predators, or it may act as a protective layer for the embryo to prevent damaging solar radiation, water loss, and bacterial infections (Moreno and Osorno 2003;Kilner 2006;Cherry and Gosler 2010;Maurer et al 2011). Recent studies have suggested that egg colour may have thermoregulatory benefits (Wisocki et al 2020), and that egg pigmentation may be associated with the variation in nest type across species (Nagy et al 2019). Nest types can have a large impact on embryo survival, whereby well-structured nests (e.g., with a roof) will provide greater protection, warmth, and camouflage than exposed nests (e.g., open cups).…”
mentioning
confidence: 99%
See 2 more Smart Citations